Debt Equity Swaps; Trends In Equity Investments Since Marte - Anna H. Connard (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1990)
SUMMARY The discussion focusses on developments in the debt/equity swap market since the Marte project was negotiated in early 1988. It emphasises carrying forward the recent market trends to anticipate the breadth and scope of debt/equity conversions for mine development in the 1990s. Secondary market prices of LDC paper, conversion values and political influences in the host countries and the use of near debt and commodity-based instruments as components of mine financing in debt/equity deals will be placed in the perspective of recent trends and expectations for the future. THE MARTE PROJECT The Marte mine is a gold porphyry deposit in Chile's high Atacama, for which financing was put together at the beginning of 1988. The Marte project was financed by a combination of common equity and loans. It was unusual that the equity infusions were made under different programs. Some of the international equity was infused with fresh funds via DL 600. Other common foreign equity was provided through the conversion of Chilean bank debt under Chapter XIX. On the loan side,. export credits for the import component of machinery and equipment were sought. Local bank financing was negotiated for the remainder of ' the project's anticipated cost. The debt conversion market in Chile was at its apex in terms of interest, activity and government support when the mine financing was arranged. The price of Chilean paper in the secondary market hovered about 62 to 66 cents per U.S. dollar of face value. Meanwhile, the Chilean government was negotiating conversion redemptions significantly closer to full face value. The government differentiated between debt paper exchanged for corporate investors who had sourced that paper in the secondary market, and debt paper held by bank investors who would incur a transaction loss in the conversion. The use of a combined DL 600lChapter XIX equity financing created different yield calculation bases for the various investors. Chapter XIX prevents remittance of profits before year 5 and capital repatriation before year 11. Investors choosing this vehicle have either for a corporate policy in the target project not to declare dividends until repatriation is allowed, or they have to seek uses for the peso liquidity that would be generated through dividend declarations in the early years. However, DL 600 investors face no such waiting period on dividends, nor do they have restrictions imposed on cashing out of the investment before the 11th year. Therefore, any equity structure with components of both investment mechanisms will have inherent differences in cost basis and future income flows for the various participants. This equity imbalance is defensible if the investment motivations of the parties are analyzed: a mining investor using fresh funds looks for a hurdle return on equity calculated at conservative commodity prices, with as much flexibility to reap upside benefits as possible; a mining investor choosing to invest through a debt conversion mechanism will realize a modest short term gain on the conversion, reducing his effective cost basis, but sacrificing some return because of the waiting period on repatriation of dividends. INVESTMENT OBJECTIVES A bank investor exchanging his own paper for an equity participation in a mining project realizes a conversion loss on the transaction. He seeks a risk adjusted acceptable hurdle rate of return to recoup that loss over time. Motivation for the bank investor to take that loss may be derived partly from a strategy to diversify its existing portfolio by internal policy and externally regulated guidelines. The bank will compare yields on its loan portfolio to that country with anticipated dividend flows discounted back at a risk adjusted rate. It will analyze the project with return objectives of yield enhancement over time and with